Eco-Friendly and Sustainable Furniture in Interiors - Rahil Vikram Singh; Deepti Pande Rana (International Journal of Sustainability, 2024)
In the realm of interior design, the imperative for sustainability has become increasingly pronounced. "Sustainable Materials and Design: Shaping the Future of Furniture for a Greener Planet" explores the pivotal role of interior designers in advancing sustainable practices and innovative design solutions within the furniture industry. This paper delves into the environmental challenges inherent in traditional furniture manufacturing methods and materials, underscoring the need for transformative change. Through an examination of emerging sustainable materials such as reclaimed wood, bamboo, recycled plastics, and bio- based composites, this study emphasizes the importance of informed material selection to minimize ecological footprints. Furthermore, it explores how interior designers can integrate eco-conscious design principles such as modular design, longevity, reparability, and circular economy approaches into their projects, thereby fostering a culture of responsible consumption and waste reduction. Through case studies and industry examples, this paper showcases the pivotal role of interior designers as agents of change in steering the furniture industry towards a more sustainable trajectory. By embracing sustainable materials and design strategies, interior designers can not only enhance the aesthetic appeal of spaces but also contribute significantly to the creation of healthier, more environmentally friendly environments for generations to come.
Keywords: Bamboo; Ecological degradation; Environmental impact Furniture Construction; sustainable materials